Anti-Radical Activity Test of Fractions from Ashitaba Herbs (Angelica keiskei) - Permatasari, Ni Made Ayu Dinda; Muliasari, Handa; Hanifa, Nisa Isneni; Hidayati, Agriana Rosmalina; Hidajat, Dedianto; Hajrin, Wahida; Rizkika, Adila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acne vulgaris is a chronic inflammation of the skin’s pilosebaceous unit, caused by oxidative stress due to reactive oxygen species (ROS) release. Oxidative stress conditions can be treated using natural antioxidants, namely ashitaba (Angelica keiskei). In contrast to previous studies that tested column chromatography fraction of the macerated ethanol extract, this study examined the liquid-liquid partition fraction of 80% methanol sonicated extract of Ashitaba herb. This study aims to determine the antiradical activity of various fractions of Ashitaba herb extract against 1,1-diphenyl-2-picrylhidrazyl (DPPH) free radicals. 80% methanol extract of the Ashitaba herb was fractionated using chloroform, ethyl acetate, and water solvents. Each ashitaba herb fraction was identified for the content of flavonoids and phenolic compounds and the antiradical DPPH activity was tested with ascorbic acid standard using a UV-Vis spectrophotometer. The IC50 value of each fraction was statistically analyzed using One-Way ANOVA and Posthoc Tukey. The results of phytochemical identification showed that ashitaba herb fractions positively contain flavonoids and phenolics. Antiradical activity of the chloroform, ethyl acetate, and water fractions against DPPH was indicated by IC50 values of 164.22±5.68 ppm (moderate); 8.70±0.12 ppm (very strong); and 243.60±8.14 ppm (weak). Statistically, each ashitaba herb fraction differed significantly from ascorbic acid (IC50 2.37±0.05 ppm). The ethyl acetate fraction has the strongest antioxidant activity and is in the same category of antioxidant strength as the ascorbic acid standard.